2008
DOI: 10.1080/00986280802186151
|View full text |Cite
|
Sign up to set email alerts
|

Conquering Mnemonophobia, With Help From Three Practical Measures of Memory and Application

Abstract: Recent articles in Teaching of Psychology have endorsed the classroom use of various mnemonic techniques. Yet a degree of mnemonophobia (i.e., fear of using mnemonics) may persist in the minds of some ToP readers due to various lingering misconceptions. In this regard, we conducted 3 practical experiments with college students using the mnemonic keyword method to learn a set of psychological terms (namely, phobias, for which we provide a sample set, along with their mnemonic representations). We examined stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…The results of this study have revealed that with immediate recall, participants recalled a significantly higher number of Spanish meanings of Basque words at one week, than participants with no immediate recall. This result is in agreement with studies where half of the participants had delayed recall, and the other half both immediate and delayed recall (Carney & Levin, 1998, 2008Wang & Thomas, 1995;Wang et al, 1992Wang et al, , 1993. Moreover, the classmate-generated keyword group recalled more meanings of Basque words at one week than the researcher-supplied keyword group, or the participant-generated keyword group.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of this study have revealed that with immediate recall, participants recalled a significantly higher number of Spanish meanings of Basque words at one week, than participants with no immediate recall. This result is in agreement with studies where half of the participants had delayed recall, and the other half both immediate and delayed recall (Carney & Levin, 1998, 2008Wang & Thomas, 1995;Wang et al, 1992Wang et al, , 1993. Moreover, the classmate-generated keyword group recalled more meanings of Basque words at one week than the researcher-supplied keyword group, or the participant-generated keyword group.…”
Section: Discussionsupporting
confidence: 90%
“…Alternatively, in other studies half of the participants remembered immediately and in the long-term, and the other half remembered only in the long-term in order to analyse the effect of immediate recall on delayed recall. In all of the studies, immediate recall influenced delayed recall (Carney & Levin, 1998, 2008Wang & Thomas, 1995;Wang et al, 1992Wang et al, , 1993. There were no significant differences between rote learning and keyword mnemonics, and rote learning even outperformed keyword mnemonics when there was delayed recall without immediate recall, (Carney & Levin, 1998, 2008Wang & Thomas, 1995;Wang et al, 1992Wang et al, , 1993.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…They concluded that keyword mnemonics may be most helpful for foreign language learning and expressed concerns about the shorter-term nature of the learning. Yet some research has in fact demonstrated long-term learning, with transfer to applied assessments, for the keyword technique (e.g., Carney & Levin, 2008). Additional studies are needed to determine the best fit of specific mnemonic strategies to different types of content and learning environments.…”
Section: Learning Strategies From Applied Memory Researchmentioning
confidence: 99%